GDP-Inflation cyclical similarities in the CEE countries and the euro area - Corrado Macchiarelli (European Central Bank (ECB), 2013)
In this paper we look at business cycles similarities between CEE countries and the euro area. Particularly, we uncover GDP-inflation cycles by adopting a trend-cycle decomposition model which allows the trend to be either stochastic or deterministic i.e. of the non-linear type. Once cyclical components are derived, we test for ex post restrictions at both with-in (GDP-to-inflation) and cross-country (CEECs vs. euro area) levels. Allowing for different degrees of cyclical similarity, we find that a similar inflation vs. GDP cycle is not rejected only for Poland, Lithuania, Romania and Estonia (with Latvia and the euro area being at the boundary). Looking at cross-country results, almost all countries feature a fair degree of similarity with respect to the euro area. Exceptions are Poland, Hungary, Latvia and Slovenia because of lack of a similar cycle either occurring in GDP or inflation, yet not in both. Finally, observing how concurrence between each CEECs cycle and the euro area evolved over time, we find that inflation conditional correlation increased stemming from the EU accession of most CEECs and as a result of the commodity price shock preceding 2008. Further, inflation and GDP conditional correlations receded during the course of 2009-2010, possibly resulting from more idiosyncratic adjustments in the aftermath of the crisis on the monetary/fiscal side. Interestingly, Slovenia, Slovakia, Estonia and Bulgaria display a conditional correlation pattern in GDP and inflation which roughly suggest a strong out-of-phase recovery starting from 2005.
Keywords: C51; E31; E32; F43; F44; 330; business cycle; CEECs; convergence; euro area; Inflation-GDP gaps